IS RUSSIA READY FOR THE INTRODUCTION OF THE NATIONAL REFERENCE PRICING SYSTEM? - V. V. Omelyanovskiy (IRBIS LLC, 2015)
the analysis of foreign pricing and drug supply public funding systems (or a so-called drug reimbursement) shows a substantial variety and presence of national peculiarities; however the majority of the developed foreign countries apply reference pricing. As part of the introduction of reference pricing, internal and external price regulation can be distinguished. External referencing system has been used in Russia for several years already, while national or internal reference pricing system hasn't been applied until recently. The introduction of the notion of interchangeability of drugs at the legislative level creates the preconditions for a deeper study of advantages and disadvantages of this system, as well as the possibility of its use in the Russian Federation. This article describes various options for the introduction of this system, its advantages and limitations.